The Analysis of Deixis in the Novel The Fault In Our Stars by John Green - Putri, Artika; Budiarsa, Made (Humanis, 2018)
This research  entitled The Analysis of Deixis in The Novel The Fault in Our Stars by John Green. Deixis is a study to describe the relation between language and contexts in language structure itself. The objectives of this study are (1) to find out and identify types of deixis in the novel The Fault in Our Stars (2) to analyze the function of each deixis type found in the novel The Fault in Our Stars . The data were collected using documentation and observation methods using the reading and note taking techniwques. Qualitative method was used to analyze the data and the method were done by descriptive technique. The method of presenting the result of data analysis was the descriptive method and was done by argumentative technique. The result of the research shows that there are three types of deixis found in the novel The Fault in Our Stars by John Green, namely person deixis, spatial deixis and temporal deixis. Person deixis consists of first person, second person and third person. The first person deixis is used to identify the speaker. The second person deixis is used to show the addressee. The third person deixis is used to show the referent not identified as the speaker or the addressee. The spatial deixis is used to describe a location participant in speech event. Temporal deixis is used to point a certain period of time.